Pengaruh Pemberian Terapi Murrotal Al-Qur’an Terhadap Penurunan Dismenorea ada Remaja Putri di SMAN 9 Kendari - Khair Anwar, Khalidatul; Refsi, Dian; Syahrianti, Syahrianti (Poltekkes Kemenkes Kendari, 2021)
Efforts to deal with dysmenorrhea in adolescent girls can be done by non-pharmacological methods, namely distraction therapy through the provision of listening to Al-Qur'an reading therapy (murottal Al-Qur'an) which can have a healing effect on physical and spiritual diseases. The study purpose was to determine effect of murrotal Al-Qur'an therapy on reducing dysmenorrhea in adolescent girls at SMAN 9 Kendari. This research is a quantitative study, with an experimental design and using a pretest-posttest with control group design. Researchers compared pain before and after being given therapy for 15 minutes and a 5 minute rest period for post-test measurements. The study population were all female students who experienced dysmenorrhea in grades X and XI totaling 115 people. Sampling technique in study used a probability sample with a systematic random sample method. The number of samples in this study were 36 people. The data collection tool used is an observation sheet using the Numeric Rating Scale (NRS) pain intensity scale. Analysis of the data used Wilcoxon test. The results showed that p value (0.000) < ? (0.05) then Ha was accepted and H0 was rejected so that there were differences in results before and after giving murrotal Al-Qur'an therapy. It can be concluded that there is an effect of murrotal Al-Qur'an therapy on the reduction of dysmenorrhea.